PEMBUATAN ATLAS BABAD TANAH JAWI HALAMAN SAMPUL DEPAN (PERIODE KERAJAAN PAJANG DAN MATARAM) BERDASARKAN ANALISIS TOPONIM - , TRI UTAMI H, Dr. Heri Sutanta ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Historical journeys have always been written in many forms of references by indigenous or international researcher. Babad Tanah Jawi is a well-known Javanese Classic literature learnt by historians and scholars. Spatial aspect is necessary to support historical studies. In doing so, changes in toponyms due to historical circumstances were evaluated. With regard to Babad Tanah Jawi, currently there is no historical atlas developed. The aims of this project is to visualize the spatial aspect of Babad Tanah Jawi literature using atlas, incorporating assessment of changes in toponyms. By focusing on the creation of an atlas, the textual references were transferred into maps and table. Toponym analysis was conducted and its results were shown in a table to track their changes, while the maps were used to help the reader to understand the historical story written in the references. Textual references and attribute data were combined with spatial data such as administration maps and topographic maps. Mapping and graphic software were used for the merging two types of data. Historical journeys that can be summarized from the textual references were reconstructed with the historical thematic maps. The results were evaluated by historian familiar with the story. The result of this project is an Atlas of Babad Tanah Jawi in the Period of the Kingdom of Pajang and Mataram. The Atlas is presented with maps which give the general view of the story of Babad Tanah Jawi and the summaries of the story. There are 19 thematic maps developed. Besides atlas, this research produces toponyms table which is depict the changes in toponyms and explanation based on the textual references. Toponym analisys, which was verified with several independent sources, shows that there were 79 toponyms changes and 47 remain.